Study of Moral Educational Values Contained in Kololi Kie Culture in Salero Ternate Village, North Maluku - Alya Indriani; Prihma Sinta Utami (PT ARRUS Intelektual Indonesia, 2023)
This research was conducted to know the values of moral education contained in the kololi kie culture in Salero Village. The research method used in this study is a type of descriptive qualitative research. Data collection techniques were used using interviews and documentation. The research subject used in this study was the traditional chairman of the village of Salero. The results of the research that has been carried out produce several studies about the value of moral education in the Kololi Kie culture as follows: a) the Kololi Kie culture teaches the strategic role of moral education in society to appreciate and preserve local culture; b) kololi kie culture as an effort to strengthen the moral education of religious attitudes in society with a philosophy of expression of gratitude in every activity; c) the kololi kie cultural ritual by going around the island is interpreted as strengthening the moral education of the people to love their nation and defend the region from external threats including global cultural influences; d) the kololie culture has a philosophy of moral education to teach tolerance with society and strengthen community ties; e) Kololi Kie culture describes the meaning of moral education, namely tolerance, togetherness, cooperation and religious.